The effect of soil saturated culture and aerobic system on rice physiological characteristics. A research / Shairul Rizabarma Omar - Omar, Shairul Rizabarma (Faculty of Plantation and Agrotechnology, 2018)
Paddy (Oryza sativa) is one of the cereals and is a staple food for many people in the world. In Malaysia, the cultivated rice is divided into two types, namely paddy fields which are also known as rice fields and upland rice. Several water-saving systems for paddy cultivation have been identified to reduce irrigation problems occurring almost throughout the agricultural area for paddy cultivation, among which are aerobic systems and saturated soils. The objective of the study was to identify the effects of water-saving systems on the rate of growth of trees and yields of rice. The variety of paddy used is the high yield variation produced by MARDI namely MR219 and MR263 which proved to have resistance to some pests and diseases. The experiment was arranged into three blocks in random condition in a greenhouse at Universiti Teknologi MARA (UiTM), Jasin Campus for 14 weeks during the cultivation period. Each rice variety has three types of treatments and each treatment has four replications. Some data on tree growth rates were recorded for analysis using Minitab software in two directions ANOVA. The results showed significant differences in water use and led to the growth of weeds in saturated soil treatment paddy fields and aerobic systems compared to ordinary planting. At the height of the crop shows a slight difference between each treatment and the saturated soil system records high chlorophyll content reading other than treatments.